Quantification of in-season high-intensity running in young soccer players - Hidalgo-de Mora, J.; López-Segovia, M.; Campos-Vázquez, M. A.; Pareja-Blanco, F. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: During the past decade, high-intensity running has exponentially increased throughout soccer matches (1, 2), being considered a key factor in elite soccer (3). In this regard, elite soccer players spend longer times at low speeds across training sessions compared to those attained during matches (4, 5). Therefore, the aim of this study was to compare the training load and high-intensity running recorded during training sessions and official matches.